On the line [videorecording (DVD)] - Boulanger, Romuald; Gibson, Mel; Moseley, William, 1987-; O'Neill, Alia Seror; Spera, Paul; Farès, Nadia, 1973-; Arce, Enrique; Dillon, Kevin (Paramount, 2023)
Mel Gibson stars as a provocative and edgy overnight radio host who must play a dangerous game of cat and mouse with a mysterious caller who has kidnapped his family and is threatening to kill them and blow up the whole station, all while live on air.